A Thorough Examination of PBB-P2 Potential and Its Pertinence to Local Revenue and Taxpayer Compliance in Badung Regency - Subagia, I Wayan Gede Subagia; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (PT Mattawang Mediatama Solution, 2025)
The objective of this study is to analyze the impact of the Rural and Urban Land and Building Tax Potential (PBB-P2) and its relevance to local revenue (PAD) and taxpayer compliance in Badung Regency, both directly and indirectly. The present study employs a quantitative approach, utilizing the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. Primary data was obtained through the distribution of questionnaires to 160 respondents who are active PBB-P2 taxpayers in Badung Regency. The findings indicated that PBB-P2 Potential and PBB-P2 Relevance exert a substantial influence on PAD. However, it is important to note that only PBB-P2 Relevance has been demonstrated to have a significant effect on Taxpayer Compliance, both directly and indirectly through PAD. Conversely, PBB-P2 Potential exerts minimal influence on Taxpayer Compliance, either directly or through PAD. PAD has been demonstrated to exert a substantial influence on taxpayer compliance, functioning as a pivotal mediator in the association between PBB-P2 relevance and taxpayer compliance. This finding suggests that taxpayers' perceptions of tax transparency and usefulness play a more significant role in encouraging compliance than the amount of regional fiscal potential. Consequently, the strategy to enhance taxpayer compliance must prioritize initiatives that cultivate public trust, ensure transparency in tax administration, and optimize the practical application of PAD in public services